Field dependence of the magnetocaloric effect in core-shell nanoparticles - Franco, V.; Conde, A.; Sidhaye, Deepti; Bhagavatula L. V. Prasad; Poddar, P.; Srinath, S.; Phan, M. H.; Srikanth, H. (Journal of Applied Physics, 2010)
The field dependence of the magnetic entropy change peak at the low temperature surface spin freezing transition in chemically synthesized, monodispersed Co, Co-Ag, and Ni-Ag core-shell nanoparticles is studied, with the aim of gaining insight into the critical exponents of this transition. It is evidenced that although the magnitude of the peak entropy change and position of the peak can be tuned by changing the composition and nature (metallic or organic) of the shell and surfactant layers, the characteristics of the spin freezing transition are not altered. The field dependence of the refrigerant capacity also confirms this finding. (C) 2010 American Institute of Physics. [doi: 10.1063/1.3335514]